Co-producing an action-oriented framework for community-based Physical Activity Promotion in Germany. (11th December 2021) - Kohler, Simone; Helsper, Natalie; Dippon, Lea; Rütten, Alfred; Abu-Omar, Karim; Pfeifer, Klaus; Semrau, Jana
Summary: German National Recommendations for Physical Activity (PA) and PA Promotion recommend community-based approaches to promote PA at the local level with a focus on health equity. In addition, the German Federal Prevention Act addresses health equity and strengthens setting-based health promotion in communities. However, the implementation of both in the local context remains a challenge. This article describes Phase 1 of the KOMBINE project that aims to co-produce an action-oriented framework for community-based PA promotion focusing on structural change and health equity. (i) In a series of workshops, key stakeholders and researchers discussed facilitators, barriers and needs of community-based PA promotion focusing on health equity. (ii) The research team used an inductive approach to cluster all findings and to identify key components and then (iii) compared the key components with updated literature. (iv) Key components were discussed and incorporated into a gradually co-produced framework by the participants. The first result of the co-production process was a catalog of nine key components regarding PA-related health promotion in German communities. The comparison of key components with scientific evidence showed a high overlap. Finally, a six-phase action-oriented framework including key components for community-based PA promotion was co-produced. The six-phase action-oriented framework integrates practice-based and scientific evidence on PA-related health promotion and health equity. It represents a shared vision for the implementation of National Recommendations for PA and PA Promotion in Germany. The extent to which structural changes and health equity can be achieved is currently being investigated in pilot-studies. Lay Summary: This paper describes how the participants in the KOMBINE project were involved in an innovative approach to transfer the German National Recommendations for Physical Activity (PA) and PA Promotion into the local practice of communities. Scientists, politicians and community actors (e.g. mayors, heads of sports departments) discussed their knowledge and experiences of facilitators, barriers and needs to promote PA in communities, specifically for people in difficult life situations (e.g. individuals with social disadvantages). Based on the results, they jointly developed key components and an action-oriented framework to implement the National Recommendations for PA and PA Promotion in German communities.